KARET PALEMBANG: Perseteruan Pusat dan Daerah Tahun 1950-an - Ryllian Chandra (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2016)
This article discusses the political impact and confrontation as consequences of the central government's efforts to control the rubber trade of Palembang. Rubber was main commodity produced from Palembang that gave economic benefits are not only for Palembang itself but also the national economy. However, the gain from rubber industries was not encourage development in the region. It has risen the demands of regional autonomy and led uprising in some regions.